2012
DOI: 10.1021/jp304650s
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Properties of Gecko-Inspired Mimetic via Micropatterned Carbon Nanotube Forests

Abstract: The adhesive properties of the gecko foot have inspired designs of advanced micropatterned surfaces with increased contact areas. We have fabricated micropatterned pillars of vertically aligned carbon nanotube forests with a range of pillar diameters, heights, and spacings (or pitch). We used nanoindentation to measure their elastic and orthogonal adhesion properties and derive their scaling behavior. The patterning of nanotube forests into pillar arrays allows a reduction of the effective modulus from 10 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 52 publications
0
48
0
6
Order By: Relevance
“…The presence of pull-off forces found by other authors can be explained with different testing methods and VACNT arrangements [19,20,22,38]. Testing of adhesion of VACNTs by pressing with a plate led to an anisotropic alignment of the tips of the 200-500 µm long CNTs in parallel to the test surface [20].…”
Section: Absence Of Pull-off Forcesmentioning
confidence: 80%
See 3 more Smart Citations
“…The presence of pull-off forces found by other authors can be explained with different testing methods and VACNT arrangements [19,20,22,38]. Testing of adhesion of VACNTs by pressing with a plate led to an anisotropic alignment of the tips of the 200-500 µm long CNTs in parallel to the test surface [20].…”
Section: Absence Of Pull-off Forcesmentioning
confidence: 80%
“…The latter was later predicted by Finite Element Analysis [38]. Chen et al [22] reported significant pull-off forces from micro-patterned 170-230 µm high VACNT pillar-like arrays, and an influence of pillar aspect ratio and spacing on both EEM and adhesion strength. Mechanical testing on 65 µm thick films of VACNT brushes using sharp SPM tips resulted in adhesion forces of 1.6 × 10 -2 nN nm -2 , which was 200 times higher than those of the gecko foot-hairs [19].…”
Section: Absence Of Pull-off Forcesmentioning
confidence: 94%
See 2 more Smart Citations
“…Adhesion is observed in a loaddisplacement curve as a region of negative load during unloading [62][63]. The principle of this experiment is to put into contact the diamond probe tip and the flat polymer substrate and determine the maximum pull-force necessary to separate both materials.…”
Section: Adhesion Energymentioning
confidence: 99%